Financial Performance of Health Service Providers Sub-Industry Companies Before and During the Covid-19 Pandemic - Fiscarina, Keke Dana; Paranita, Ekayana Sangkasari (Journal of Applied Management Research, 2023)
This study aims to analyze differences in financial performance before and during the Covid-19 pandemic based on liquidity, solvency, profitability, and activity ratios. The novelty of this research is a comprehensive analysis of financial performance before the Covid-19 pandemic compared to performance during the Covid-19 pandemic at the beginning of the period, namely 2020 until the second year of the pandemic, namely 2021. The research population is fourteen health service provider sub-industry companies listed on the Indonesia Stock Exchange. Based on the purposive sampling method, nine companies were selected as samples. Data sources are secondary data in the form of balance sheets and income statements. Liquidity performance is measured by the Current Ratio, solvency performance is measured by the Debt to Equity Ratio, profitability performance is measured by Return on Equity, and activity performance is measured by Total Assets Turnover. The analysis technique includes the normality test with the Kolmogorov-Smirnov test and hypothesis testing using the paired sample t-test. The results of the study concluded that there were no significant differences in liquidity, solvency, and activity performance before and during the first and second years of the Covid-19 pandemic. As for the profitability performance, it has been proven that there is a significant difference, namely that the performance during the first and second years of the Covid-19 pandemic was relatively higher than before the Covid-19 pandemic